Development of an assessment scale for engagement in activities for patients with moderate to severe dementia. Issue 3 (1st March 2021) - Tanaka, Hiroyuki; Umeda, Ren; Shoumura, Yuko; Kurogi, Tatsunari; Nagata, Yuma; Ishimaru, Daiki; Yoshimitsu, Koji; Tabira, Takayuki; Ishii, Ryouhei; Nishikawa, Takashi
Abstract: Background: Various types of therapy, including occupational therapy, are utilised for the treatment of moderate to severe dementia. In order to determine the optimal rehabilitation strategy for such patients and examine the treatment efficacy, an assessment scale for engagement in various group activities that can be easily applied in clinical situations is required. We herein report the development of the Assessment Scale for Engagement in Activities (ASEA) and its clinical utility. Methods: The ASEA was developed by nine occupational therapists and a psychiatrist with experience in developing measures for dementia, in accordance with the COSMIN (COnsensus‐based Standards for the selection of health status Measurement INstruments) checklist. This assessment comprises 10 items covering four domains: Engagement in the Activity, Interaction, Arousal, and Affect. Participants with moderate to severe dementia who resided in a psychiatric acute phase hospital in Japan were assessed in terms of engagement in activities using the ASEA and Todai‐shiki Observational Rating Scale (TORS), and in terms of cognitive function using the Mini‐Mental State Examination (MMSE). We examined the internal consistency, inter‐ and intra‐rater reliability, content validity, and concurrent validity of the ASEA. Results: Cronbach's alpha of the ASEA was 0.889. The overall inter‐rater reliability was 0.937 (Spearman rank correlation, P  < 0.001), and the intraclass correlation (ICC) for each item was 0.490–0.965 ( P  < 0.018–0.001). The overall test–retest reliability was 0.778 (Spearman's rank correlation, P  < 0.001), and the ICC for each item was 0.498–0.863 ( P  < 0.023–0.001). The test–retest correlations were significant for almost all items, aside from 'Interaction with others' ( P = 0.051). The concurrent validity, examined using the TORS and MMSE, was 0.920 and 0.304 (Spearman's rank correlation, P  < 0.001–0.006). Conclusions: The ASEA has confirmed reliability and validity, aside from 'Interaction with others' regarding test–retest reliability. Generally, this assessment tool has clinical utility and allows the evaluation of activity engagement among patients with moderate to severe dementia.